The constitutional invalidity of warrantless drugs searches in South Africa - Parpworth, Neil (2018)
In some jurisdictions, where individual privacy and property rights are afforded constitutional protection, legal disputes regarding police powers of entry and search sometimes extend beyond the law of tort into public law, where the challenge is to the power itself. The South African Constitutional Court has determined the constitutional validity of warrantless powers of entry and search on a number of occasions. This article discusses the most recent addition to this body of case law, as well as several related authorities from other jurisdictions. Where appropriate, reference to the position in English law also forms part of the discussion. - Reproduced.
Keywords: Drug trafficking - South Africa; Drugs - South Africa